2018
DOI: 10.1186/s13068-018-1262-1
|View full text |Cite
|
Sign up to set email alerts
|

Lignin–carbohydrate complexes: properties, applications, analyses, and methods of extraction: a review

Abstract: The complexity of lignin and hemicellulose segmentation has been known since the middle of the ninetieth century. Studies confirmed that all lignin units in coniferous species and 47–66% of lignin moieties in deciduous species are bound to hemicelluloses or cellulose molecules in lignin–carbohydrate complexes (LCC). Different types and proportions of lignin and polysaccharides present in biomass lead to the formation of LCC with a great variety of compositions and structures. The nature and amount of LCC linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 406 publications
(203 citation statements)
references
References 154 publications
(382 reference statements)
2
198
1
2
Order By: Relevance
“…Szczerbowski et al (2014) reported lower values for unidentified cellulose derivative, anhydrohexose, at 1% after acid treatment of bagasse. In our study, the unidentified compounds at 49% of the bagasse extract may be attributed to water-soluble polysaccharides, lignin-carbohydrates complexes (Tarasov et al, 2018), acetyl groups derived from xylan (Carvalho et al, 2015) and organic acids. Lignin-carbohydrate complexes are molecules with hemicellulosic backbone covalently bonded to small lignin fragments from plant cell walls that are sometimes extracted during subcritical water conditions such as HTL (Mart ınez-Abad et al, 2018).…”
Section: Composition Of the Bagasse Extracts From Htlmentioning
confidence: 57%
“…Szczerbowski et al (2014) reported lower values for unidentified cellulose derivative, anhydrohexose, at 1% after acid treatment of bagasse. In our study, the unidentified compounds at 49% of the bagasse extract may be attributed to water-soluble polysaccharides, lignin-carbohydrates complexes (Tarasov et al, 2018), acetyl groups derived from xylan (Carvalho et al, 2015) and organic acids. Lignin-carbohydrate complexes are molecules with hemicellulosic backbone covalently bonded to small lignin fragments from plant cell walls that are sometimes extracted during subcritical water conditions such as HTL (Mart ınez-Abad et al, 2018).…”
Section: Composition Of the Bagasse Extracts From Htlmentioning
confidence: 57%
“…The loss of carboxyl group of glucuronic acid residues in hemicellulose probably indicates the partial loss of unconjugated ester linkages in lignin-carbohydrate complexes (LCCs) of VICWs in archaeological wood according to a previous report [14]. It is known that the covalent link between the carboxyl group of glucuronic acid residue in hemicelluloses and α-hydroxyl group of the lignin represents one kind of covalent links in LCCs [26,27]. In addition, the weak Py-GC/MS signal 2 (2-butenal), weak signal 3 (2-furan methanol) and weak signal 5 (2-hydroxy-3-methyl-2-cyclopenten-1-one) in the pyrogram of the WAW back up these findings [17,[28][29][30][31] (Figure 3B & Table S3).…”
Section: The Deterioration Of Cell Wall Componentsmentioning
confidence: 96%
“…Stem/leaf mixtures (Gig17M, Gig34M), stems (Gig17S, Gig34S) and leaves (Gig17L, Gig34L). However, HSQC NMR only considers signals for free C-H coupling (in case of further aromatic substituents, those fragments would not be recognized) [48,63,90]. So, further detailed analysis is required to explain deviations of the monolignol ratios obtained via pyrolysis GC/MS and HSQC-NMR.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%